Metabolic clues to aging: exploring the role of circulating metabolites in frailty, sarcopenia and vascular aging related traits and diseases - Qian, Zonghao; Huang, Yuzhen; Zhang, Yucong; Yang, Ni; Fang, Ziwei; Zhang, Cuntai; Zhang, Le (Frontiers in Genetics, 2024)
Physical weakness and cardiovascular risk increase significantly with age, but the underlying biological mechanisms remain largely unknown. This study aims to reveal the causal effect of circulating metabolites on frailty, sarcopenia and vascular aging related traits and diseases through a two-sample Mendelian Randomization (MR) analysis. Exposures were 486 metabolites analyzed in a genome-wide association study (GWAS), while outcomes included frailty, sarcopenia, arterial stiffness, atherosclerosis, peripheral vascular disease (PAD) and aortic aneurysm. Primary causal estimates were calculated using the inverse-variance weighted (IVW) method and a total of 125 causative associations between metabolites and outcomes were identified. Methods including MR Egger, weighted median, Q-test, and leave-one-out analysis were used for the sensitive analysis. After correcting of false discovery rate (FDR) and performing sensitive analyses, seven strong causal links were ultimately identified between six metabolites (kynurenine, pentadecanoate (15:0), 1arachidonoylglycerophosphocholine, androsterone sulfate, glycine and mannose) and three diseases (sarcopenia, PAD and atherosclerosis). Besides, metabolic pathway analysis identified 13 significant metabolic pathways in 6 age-related diseases. Furthermore, the metabolite-gene interaction networks were constructed. Our research suggests that the identified metabolites hold promise as valuable biomarkers for frailty, sarcopenia and vascular aging related traits and diseases.